KOMPONEN- KOMPONEN KURIKULUM DI ERA KURIKULUM: ANTARA OTONOMI GURU DAN STANDAR NASIONAL - Tantri (Jurnal Komunikasi, 2026)
The implementation of Kurikulum Merdeka marks a significant transformation in Indonesia’s education system by positioning teacher autonomy as a central pillar of learning. This curriculum is designed to provide flexibility for educational institutions and teachers to develop contextual, differentiated, and student-centered learning processes. Nevertheless, such autonomy remains within the framework of national regulations established by the government through the Standar Nasional Pendidikan. This study aims to analyze the key components of the curriculum in the era of Kurikulum Merdeka and to examine the dynamics between teachers’ pedagogical freedom and national regulatory demands. The main components analyzed include learning objectives, curriculum structure, assessment, teaching materials, and the strengthening of the Pancasila Student Profile. The study employs a literature review method with a descriptive-analytical approach. The findings indicate that Kurikulum Merdeka promotes a balance between flexibility in classroom implementation and quality accountability through structured graduate competency standards and learning outcomes. Therefore, the successful implementation of this curriculum largely depends on teachers’ professional capacity to translate policy into innovative, reflective, and adaptive teaching practices that respond to students’ needs.